Biologic Therapy Carries a Very Low Risk of Reactivation in Hepatitis B Surface Antigen-Negative Phase of Hepatitis B - Ergenç, İlkay and Kani, Haluk Tarık and Karabacak, Murat and Cömert Özer, Elif and Mehdiyev, Shahin and Jafarov, Fuad and Abacar, Kerem Yiğit and Kutluğ Ağaçkıran, Seda and Sevik, Gizem and Aslan, Rahmi and et al. (Turkish Journal of Gastroenterology, 2022)
Background: The risk of hepatitis B reactivation in hepatitis B surface antigen-negative phase of hepatitis B virus-infected patients exposed to biologic agents is not clear. We aimed to investigate the reactivation rate in hepatitis B surface antigen-negative phase of hepatitis B virus-infected patients after biologic therapy. Methods: Patients followed at gastroenterology, rheumatology, and dermatology clinics with a diagnosis of immune-mediated inflammatory diseases were screened. Immune-mediated inflammatory diseases patients exposed to biologic agents with a negative hepatitis B surface antigen and positive hepatitis B core immunoglobulin G antibody were included in the study. Results: We screened 8266 immune-mediated inflammatory disease patients, and 2484 patients were identified as exposed to biologic agents. Two hundred twenty-one patients were included in the study. The mean age was 54.08 ± 11.69 years, and 115 (52.0%) patients were female. The median number of different biologic subtype use was 1 (range: 1-6). The mean biologic agent exposure time was 55 (range: 2-179) months. One hundred and fifty-two (68.8%) patients used a concomitant immunomodulatory agent, and 84 (38.0%) patients were exposed to corticosteroids during biologic use. No hepatitis B reactivation with a reverse seroconversion of hepatitis B surface antigen positivity was seen. Antiviral prophylaxis for hepatitis B was applied to 48 (21.7%) patients. Hepatitis B virus-DNA was screened in 56 (25.3%) patients prior to the biologic exposure. Two patients without antiviral prophylaxis had hepatitis B virus-DNA reactivation with a negative hepatitis B surface antigen during exposure to the biologic agent. Conclusion: We found 2 reactivations and no hepatitis B surface antigen seroconversion in our cohort. Antiviral prophylaxis for patients exposed to biologic agents may need to be discussed in more detail. Cite this article as: Ergenç İ, Kani HT, Karabacak M, et al. Biologic therapy carries a very low risk of reactivation in hepatitis B surface antigen-negative phase of hepatitis B. Turk J Gastroenterol. 2023;34(2):156-160.